Study of Petiole Anatomy and Pollen Morphology of Five Species of Senna Mill. From Bangladesh - Doty, Mabia Khanom; Rashid, Parveen; Shethi, Kishwar Jahan (Dhaka University Journal of Biological Sciences, 2020)
Abstract Not Available Dhaka Univ. J. Biol. Sci. 29(2): 245-252, 2020 (July)